Application of Biogasoline in a Four-stroke Motorcycle Engine - Sutrisna Saputra; Karna Wijaya; Mudjijana (Universitas Gadjah Mada, 2020)
The problems facing the world, in relation to the increasing consumption of petroleum and its limited sources, as well as pollution by fuel-related gases, such as CO, have sparked research on the application of biogasoline as an environmentally friendly alternative fuel. Our research aimed to determine engine performance through mixtures of biogasoline and gasoline to measure torque, power, and fuel consumption rate, and to determine the effect of the mixture on the level of air pollution. The biogasoline used was previously prepared from cooking oil through a Cr-zeolite-catalyzed process. The testing methods on the fuel mixture as a working substance included engine performance and exhaust emission tests, applied to four-stroke engines with mixtures with gasoline and biogasoline ratios of 95:5, 90:10, and 85:15. The engine performance test results showed that the highest values of torque, power, and average effective pressure were of the fuel with a composition of 85:15. CO and HC, the two emitted gases with high toxicities, based on the air quality standard, should not be more than 5.5% by volume and 2400 ppm, respectively. In this research, the findings indicated that both substances, not exceeding 3.0% by volume and not more than 200 ppm, respectively, are safe and environmentally friendly.